Survei Pembinaan Prestasi Ekstrakurikuler Bola Tangan di SMK Kabupaten Purworejo Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
The sport of handball has developed and starting to be in great demand, especially in extracurricular activities at various schools, one of them is the Vocational High School in Purworejo Regency.. The purpose of this study was to determine the development of handball extracurricular achievements at Vocational High School in Purworejo Regency. This research used qualitative approach method, the subjects in this study were extracurricular coaches or sports teachers and the students who took part in handball extracurricular activities at Vocational High School in Purworejo Regency. The retrieval of data using purposive sampling technique with observation, interviews, and documentation as the data collection methods regarding achievement development, training programs, infrastructure, and funding for handball extracurricular activities at Vocational High School in Purworejo Regency. This study obtained some result, they were: the achievement development has gone well, the training program provided by the coach includes four aspects (physical, technical, tactical, and mental training), the facilities and infrastructure for handball extracurricular activities are adequate, it is just that the field is inadequate, the source of handball extracurricular funds is obtained from the allocation of BOS funds.